Access to Finance in Output-Based Aid - Kumar, Geeta (World Bank, Washington, DC, 2017)
Output-Based Aid (OBA) and other results-based financing mechanisms are gaining popularity in the development context for many reasons, in particular, the desire to link scarce public funding with actual results on the ground. But withholding disbursements until the delivery of 'results' or 'outputs' requires that the service providers delivering the results must have access to finance (A2F) to pay for the 'inputs' in the first place. Such finance is not always available or affordable. The purpose of this working paper is to outline some of the key issues related to OBA and A2F. The analysis focuses on the energy, water, and health sectors. Micro, small and medium enterprise (MSME) financing is the main topic; however, OBA is ultimately about poor households affording access to basic services, and many OBA schemes attempt to address A2F for households, so some of these innovations are also described. The working paper is expected to support a consultative process between experts dealing with A2F challenges and experts on OBA. This process should help raise awareness of the OBA approach among potential financiers, and help consider solutions (instruments, partnerships, capacity building) so that OBA and other similar results-based financing mechanisms can be brought to scale and integrated into broader sector policy, where appropriate.